ERRORS IN PRONOUNCING ENGLISH PHONEMES: A PRAAT ANALYSIS - Rohani Ganie; Wahyu Maulana; Rahmadsyah Rangkuti (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2019)
This article is concerned with a study of pronunciation errors made by students of English Literature Department, Faculty of Cultural Sciences, University of Sumatera Utara. The scope is limited to the study of error analysis in the pronunciation of English phonemes. The participants of this study were two students of the department with Acehnese background. In this study, the electronic software called Praat was used as an instrument in the analysis of speech sounds of the participants. The purpose of this study was to find out the dominant errors of the pronunciation of English phonemes made by the participants. The data were derived from the pronunciations of English phonemes which were recorded and transcribed in the International Phonetic Alphabet (IPA) as in Katamba (1996: 13). The standard value of the pronunciation of English phonemes was adopted from Cambridge Advanced Learner’s Dictionary. The quality of the pronunciations of the participants was described in graphs and the results were shown in percentage as given in tables and charts.